IMF Staff Papers Supplement. (IMF Staff Papers; IMF Staff Papers, 1985)
This paper presents the bibliography cover books, pamphlets, reports, and periodical articles that describe the functions, organization, and activities of the IMF. Publications on the various aspects of international economics are included only when they contain material relating specifically to the IMF. Previous bibliographies in this series that were compiled by Martin L. Loftus were published in Staff Papers. Vol. 1 (April 1951), Vol. 3 (April 1953), Vol. 4 (August 1955), Vol. 6 (November 1958), Vol. 9 (November 1962), Vol. 12 (November 1965), Vol. 15 (March 1968), Vol. 19 (March 1972), and Vol. 21 (July 1974). Mrs. Salda prepared the bibliographies that were published in Vol. 25 (March 1978), Vol. 26 (June 1979), Vol. 27 (June 1980), Vol. 29 (June 1982), Vol. 30 (September 1983), and Vol. 31 (Supplement, December 1984).